Using Dental Pulp Stem Cells for Stroke Therapy - Gancheva, Maria R.; Kremer, Karlea L.; Gronthos, Stan; Koblar, Simon A. (Frontiers in Neurology, 2019)
Stroke is a leading cause of permanent disability world-wide, but aside from rehabilitation, there is currently no clinically-proven pharmaceutical or biological agent to improve neurological disability. Cell-based therapies using stem cells, such as dental pulp stem cells, are a promising alternative for treatment of neurological diseases, including stroke. The ischaemic environment in stroke affects multiple cell populations, thus stem cells, which act through cellular and molecular mechanisms, are promising candidates. The most common stem cell population studied in the neurological setting has been mesenchymal stem cells due to their accessibility. However, it is believed that neural stem cells, the resident stem cell of the adult brain, would be most appropriate for brain repair. Using reprogramming strategies, alternative sources of neural stem and progenitor cells have been explored. We postulate that a cell of closer origin to the neural lineage would be a promising candidate for reprogramming and modification towards a neural stem or progenitor cell. One such candidate population is dental pulp stem cells, which reside in the root canal of teeth. This review will focus on the neural potential of dental pulp stem cells and their investigations in the stroke setting to date, and include an overview on the use of different sources of neural stem cells in preclinical studies of stroke and clinical trials.